Multifactorial analysis of sociodemographic and nursing factors in the context of nutritional management of preterm infants: A longitudinal study - Abrmanová, Michaela; Brabcová, Iva; Červený, Martin; Tóthová, Valérie (Kontakt, 2024)
Goals: This study aims to identify sociodemographic predictors of breastfeeding and evaluate the effect of nursing interventions on nutritional strategies in premature infants (0-6 months). Methods: A prospective monocentric longitudinal study focused on the nutritional management of 201 preterm infants. Monitoring was performed for two years at specific time intervals. Results: The mother's nationality influences the child's nutrition in the first weeks but this influence decreases with the child's age. The mother's education has a significant effect on nutritional choices. Higher education correlates with using different nutritional combinations. Strong predictors of breastfeeding include the first latch, skin-to-skin contact, and orofacial stimulation. Conclusion: The study identified vital factors influencing the nutrition of preterm infants. These findings enable better targeting of measures and support better health and development of such children. The results provide a scientific basis for the development of nutritional strategies and interventions.
Keywords: sociodemografické faktory; Lactation; laktace; náhražky mateřského mléka; Infant, Premature; longitudinální studie; Diet; dieta; Longitudinal Studies; Nutritional Physiological Phenomena; fyziologie výživy; Sociodemographic Factors; Humans; Breast Feeding; kojení; Infant Formula; novorozenec nedonošený; lidé